Current issues in inflammatory bowel disease neoplasia - Neumann, Helmut; Vieth, Michael (Histopathology, 2015)
Recent histological criteria and developments in the field of endoscopic imaging have led to higher detection rates of neoplasms in ulcerative colitis. Once a lesion is detected, endoscopic resection is recommended to guide subsequent surveillance or therapy and to gain adequate material for histological diagnosis. Further management is based on the grade of neoplasia and on whether the neoplasia is categorized as sporadic or colitis-associated. Nevertheless it may sometimes be difficult to distinguish colitis-associated neoplasms from sporadic neoplasms. A better way to report this may be ultimately classified. Here, we review endoscopic and histological parameters to help to differentiate colitis-associated neoplasia from sporadic lesions and discuss pathogenesis and therapeutic options.
EVALuna2:2101